Will Guarantee, Guarantee Companies a Door to Door Sale? - SHABBIR, JAVERIA; PARVEEN, SOBIA (The journal of contemporary issues in business and government, 2021)
The aim of the study is to understand the value perception of consumers towards cosmetic brands and the guarantees they provide for creating trust. This study seeks to identify the attitude of consumers regarding a new distribution channel for the cosmetic companies in Pakistan. Furthermore, it will help generate new business avenues for cosmetic brands to offer their products and maximize their reach to far flung areas where there are no shopping malls. The results of the study unveiled that door to door selling offers convenience, health safety in pandemic and privacy to consumers however it also poses security issues to consumers. Moreover, door to door selling has a negative perception in Pakistan and needs high efforts to change the image of door to door selling. It will help in poverty reduction in this Covid-19 Pandemic, as semi literate to literate people of every age and genders can engage in some profitable activity and thus generating income, resulting a boost in economy. Pakistan’s population is comprised majority of women. They can benefit from this study because they can do a part time job and generate income in these testing times.